The ethics of special ops raids, recoveries, reconnaissance and rebels - Baker, Deane-Peter 1972-; Herbert, Roger; Whetham, David (Cambridge University Press, 2023)
The field of military ethics has generally been attentive to emerging trends in modern warfare. Cyber, robotics and AI, for example, have inspired an abundant and flourishing literature. One trend, however, has been largely overlooked: the emergence of special operations as a prominent instrument of statecraft. Drawing extensively on historical cases and first-hand experience, the authors of this book call attention to qualities inherent in special operations - and special operators - that challenge the moral framework which has long informed conventional military operations. Moral theorists will find this analysis provocative, while practitioners - those who conduct or oversee special operations and have an interest in the moral wellbeing of special operators - can put the authors' insights to practical use. Those who simply view with fascination the opaque world of special operations will find this book illuminating